Resources synchronization in a full truckload pickup and delivery problem : an exact approach - Melchiori, Luciana; Nasini, Graciela; Montagna, Jorge Marcelo; Corsano, Gabriela (Computers and Operations Research, 2022)
In this work, the Unpaired Full Truckload Pickup and Delivery Problem with Resource Synchronization is modeled and solved, where routes must be determined to transport commodities from pickup to delivery locations by a set of vehicles, subject to timing and resource synchronization constraints, to satisfy demands at minimum cost. Unlike previous works, the use of multiple resources for loading and unloading tasks at each location are considered and appropriately managed through a representation using discrete shifts. An integer linear programming model is proposed to simultaneously solve allocation, routing and resources synchronization optimization problems. In order to improve the model performance for large size instances, diverse reformulations, including additional inequalities and symmetric-breaking constraints, are implemented and tested. Moreover, a heuristic procedure is proposed to provide good initial feasible solutions. The capabilities of the proposed approach are assessed through several examples
Keywords: Routing; Scheduling; Resources synchronization; Full truckload; Allocation